The role of securitization in mortgage renegotiation - Sumit Agarwal; Gene Amromin; Itzhak Ben-David; Souphala Chomsisengphet; Douglas D. Evanoff (Federal Reserve Bank of Chicago, 2011)
We study the effects of securitization on renegotiation of distressed residential mortgages over the current financial crisis. Unlike prior studies, we employ unique data that directly observe lender renegotiation actions and cover more than 60% of the U.S. mortgage market. Exploiting within-servicer variation in these data, we find that bank-held loans are 26% to 36% more likely to be renegotiated than comparable securitized mortgages (4.2 to 5.7% in absolute terms). Also, modifications of bank-held loans are more efficient: conditional on a modification, bank-held loans have lower post-modification default rates by 9% (3.5% in absolute terms). Our findings support the view that frictions introduced by securitization create a significant challenge to effective renegotiation of residential loans.
Keywords: D1; D8; G1; G2; 330; loan modifications; financial crisis; household finance; mortgages; securitization; Finanzmarktkrise; Haushaltsökonomik; Hypothek; Refinanzierung; Securitization; Bank; USA